202 services you can sell for big profits - Stephenson, James (Entrepreneur Press, 2005)
This book includes: Pick from 202 fascinating fields the author has scrupulously screened and researched; Learn all you need to get started and how to avoid the pitfalls that can bedevil beginners; Discover how to become a part-time entrepreneur, pocketing sizable extra income while keeping your job.